Acute Gastric Dilatation: A Transient Cause of Hepatic Portal Venous Gas—Case Report and Review of the Literature - Satya B. Allaparthi; Curuchi P. Anand (Case Reports in Gastrointestinal Medicine)
Gastric pneumatosis (GP) and hepatic portal venous gas (HPVG) have typically been thought of as an ominous radiological sign associated with a grave prognosis, and the observation of HPVG on plain abdominal radiography, ultrasonography, or computed tomography is viewed as a significant finding. It is often associated with severe or potentially lethal conditions warranting urgent diagnosis and possible surgical intervention. Early studies of HPVG based on plain abdominal radiography found an associated mortality rate of 75% primarily due to ischemic bowel. However, modern abdominal computed tomography (CT) has resulted in the detection of HPVG in an increased proportion of nonfatal and benign conditions. We report a nonfatal case of HPVG in a patient with Noonan’s syndrome due to acute gastric dilatation in the setting of gastric outlet obstruction caused by a congenital band that is extremely rare in adults.